Climate Change Scenarios for the Basque Country: wind, humidity and radiation - M. Martija-Díez; M. Martija-Díez; R. Hernández; J. D. Gómez de Segura; S. Gaztelumendi (Advances in Science and Research)
UrbanKlima2050 is up to the date the most ambitious initiative led by the Basque Country to ensure the resilience of the territory through a multi-level governance and climate action on the ground. Within the UrbanKlima2050 project, and in order to assess the evolution of climate-related variables, future projections for wind, relative humidity and solar radiation were performed for the Basque Country. Starting from the scenario projections (RCP4.5 and RCP8.5) developed by the EURO-CORDEX community, bias adjusted data are obtained. Results show a downward trend for the wind under the RCP8.5 scenario and in the late future (2071–2100) a decrease of about 4 % is projected with respect to the historical period (1980–2009). In the RCP4.5 scenario, in general, a smoother decrease appears but is still significant. The relative humidity shows a decrease overall, with the largest values in the south, but for the late future an increase is detected in the coast, especially for the RCP4.5 scenario. The solar radiation displays a generalized increase for future projections, with an increase close to 4 % for the RCP8.5 scenario, yet under the RCP4.5 scenario the tendency does not show a significant signal. These results are of interest to perform the full implementation of the Basque Climate Change Strategy 2050.